Red Admirals Vanessa atalanta (Lepidoptera: Nymphalidae) select northern winds on southward migration - Mikkola, Kauri (Entomologica Fennica, 2003)
In the autumn periods of 1994–2001, the migrations of the Red Admiral Vanessa atalanta (L.) were recorded from the Porkkala Bird Tower, 35 km SW of Helsinki, Finland. By far the best year was 1998, when 1240 migrant V. atalanta were counted. Generalized to a 100-km strip, this would mean a minimum of half a million butterflies. Radar observations indicated that a large proportion may have migrated above the visible range. The migrations took place on sunny days with cool northern winds (down to +10–13 °C). On warmer days with southern winds, V. atalanta individuals were stationary in the terrain. Other species observed to migrate south in the same way, but in much lower numbers, included Vanessa cardui (L.), Pieris brassicae (L.) and Autographa gamma (L.). These records help to resolve the “evolutionary puzzle” of why migrant butterflies and moths travel to northern latitudes when their offspring have such limited possibilities of returning to the south. Until now, the only butterfly for which high-elevation return migrations in northern winds have been known has been the American Monarch Danaus plexippus (L.). The mechanics of the flights, the migratory behaviour and their evolutionary significance are discussed in light of the literature.